PERAN DAN EFEKTIVITAS UNDANG-UNDANG PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL DALAM PENYELESAIAN TERHADAP STUDI KASUS 21/Pdt.Sus-PHI/2023/PN Smg - Nadia Asyera Parhusip; Miladia Qiya Akhmas; Muhammad Alif; Damar Ulung Bintara Santosa (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This study examines the role and effectiveness of the Industrial Relations Dispute Settlement Act in resolving labor disputes based on Case Number 21/Pdt.Sus-PHI/2023/PN Smg. This research employs a normative legal approach using statute and case approaches. Data collection techniques involve a literature review, analyzing legal regulations, legal documents, court decisions, as well as primary and secondary legal materials. The analysis is conducted qualitatively by outlining legal facts and interpreting the relevance of applicable regulations in the case. The findings reveal that the Industrial Relations Dispute Settlement Act plays a significant role in providing legal certainty but still faces challenges in its implementation, particularly regarding the efficiency and fairness of dispute resolution processes. This study offers recommendations to enhance existing legal mechanisms to optimize labor protection.